Measuring English Proficiency: Investigating How Teachers Employ Formative Tests - Alfina Damayanti; Nuraeni Nuraeni; Novalia Tanasy (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2023)
Education holds a crucial role in human life, connecting the roles of teachers and students in teaching and evaluation. Assessment, a big part of education, helps teachers understand how well students are doing as they learn. When assessing students, teachers must consider how each student learns, what they're good at, what they find challenging, and what they need to succeed in school. So, teachers must know how to do assessments well. This study aims to determine the teacher's understanding of formative assessment and how to apply formative assessment to learning English in assessing students' English skills. The method used is a descriptive qualitative method using interviews and observations. 7 English teachers from different schools were interviewed (4 teachers at SMAN 3 Maros, 1 teacher at MA Darussalam Barandasi, and 2 English teachers at SMKN 1 Maros). Meanwhile, observations were carried out once at each school. The findings show that teachers use formative assessment at the beginning, middle, and end of learning sessions to understand students' performance. Teachers see many benefits in using formative assessments, like measuring individual abilities, reaching learning goals, and understanding student needs better. Some teachers face challenges, like figuring out how each student is different, which shows they might need more help and training. Classroom observations also show that some schools do well with formative assessments, while others have problems, such as SMK 1 Maros, which has issues with students not showing up and using home-based assignments. This study suggests giving teachers more support and training to improve assessments and learning for everyone.